2017
DOI: 10.1513/annalsats.201612-947oc
|View full text |Cite
|
Sign up to set email alerts
|

Usual Interstitial Pneumonia Can Be Detected in Transbronchial Biopsies Using Machine Learning

Abstract: We demonstrate proof of principle that genomic analysis and machine learning improves the utility of TBB for the diagnosis of UIP, with greater sensitivity and specificity than pathology in TBB alone. Combining multiple individual subject samples results in increased test accuracy over single sample testing. This approach requires validation in an independent cohort of subjects before application in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 36 publications
1
49
0
2
Order By: Relevance
“…We noted variation in PC3 and R4 injury but we believe the ongoing INTERLUNG study will find that two or three 3BMB pieces will suffice (vs >10 TBB pieces suggested for histology that is still frequently nondiagnostic). This is in line with a recent study using molecular measurements to diagnose usual interstitial pneumonia in TBBs that found three to five pieces stabilized measurements . Mucosal biopsies open new avenues of research into the mechanisms operating in transplant airways and we propose expanding the ongoing observational INTERLUNG study with the goals of including at least 1000 biopsies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We noted variation in PC3 and R4 injury but we believe the ongoing INTERLUNG study will find that two or three 3BMB pieces will suffice (vs >10 TBB pieces suggested for histology that is still frequently nondiagnostic). This is in line with a recent study using molecular measurements to diagnose usual interstitial pneumonia in TBBs that found three to five pieces stabilized measurements . Mucosal biopsies open new avenues of research into the mechanisms operating in transplant airways and we propose expanding the ongoing observational INTERLUNG study with the goals of including at least 1000 biopsies.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with a recent study using molecular measurements to diagnose usual interstitial pneumonia in TBBs that found three to five pieces stabilized measurements. 35…”
Section: Discussionmentioning
confidence: 99%
“…Although TBLB can be useful in certain situations, e.g. differential diagnosis (if changes inconsistent with UIP are present, in order to confirm an alternative diagnosis) [117], prospective studies that would reliably determine the place of this method in UIP/IPF diagnosis are still lacking [29,130].…”
Section: Commentarymentioning
confidence: 99%
“…Transbronchial lung cryobiopsy (TBLC) is a new diagnostic technique [92,[122][123][124][125][126]. Its diagnostic effectiveness and complication rates are varied and depend on the experience of the person performing the procedure [123,125,[127][128][129][130][131][132][133][134][135][136][137][138][139]. The mean mortality due to this diagnostic procedure only has been estimated at 0.2%, with less frequent sudden exacerbations than in the case of SLB (1.2% vs 6.1%).…”
Section: Introductionmentioning
confidence: 99%
“…In the future we may employ a strategy combining diagnostic modalities such as TBLCB with genomic assays, such as the one currently under study for UIP. 90 Furthermore, procedural standards and techniques vary widely between institutions and practitioners with an unclear effect on DY and patient outcomes. Preprocedural planning, patient selection, and development of more refined criteria for TBLCB indications and contraindications are necessary to further delineate its position in diagnostic algorithms as well as improve test characteristics.…”
Section: Future Directionmentioning
confidence: 99%